2004
DOI: 10.2460/ajvr.2004.65.1708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat and energy on body weight and composition after gonadectomy in cats

Abstract: Weight gain in neutered cats was decreased by feeding an LF, low energy-dense diet. To prevent weight gain in cats after neutering, a suitable LF diet should be fed in carefully controlled meals rather than ad libitum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 35 publications
8
67
1
4
Order By: Relevance
“…Food intake and BW increased in all cats following ovariohysterectomy, as has been noted in other studies (Fettman et al, 1997;Harper et al, 2001;Kanchuk et al, 2003;Nguyen et al, 2004;Backus et al, 2007;Cave et al, 2007;Belsito et al, 2009). Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 62%
“…Food intake and BW increased in all cats following ovariohysterectomy, as has been noted in other studies (Fettman et al, 1997;Harper et al, 2001;Kanchuk et al, 2003;Nguyen et al, 2004;Backus et al, 2007;Cave et al, 2007;Belsito et al, 2009). Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 62%
“…Neutering alone does not seem to decrease insulin sensitivity, but rather increases the risk of obesity. Neutered cats gain weight more easily compared to intact cats,27, 28, 29 and subsequent weight gain leads to decreased insulin sensitivity 26, 30. Therefore, according to these studies, it is the increased risk of obesity after neutering that appears to be the contributing factor to the increased occurrence of DM in neutered cats 8, 31.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, according to these studies, it is the increased risk of obesity after neutering that appears to be the contributing factor to the increased occurrence of DM in neutered cats 8, 31. However, other studies show conflicting results and it remains unclear whether male or female cats are more prone to weight gain after neutering 27, 29, 32. In Sweden, more than 80% of all cats are neutered, with somewhat more male cats (88%) neutered compared to female cats (73%) 16…”
Section: Discussionmentioning
confidence: 99%
“…Felinos castrados, independente da idade, possuem menor coeficiente térmico, maior massa corpórea, escore corporal e quantidade de gordura falciforme, em comparação aos inteiros, e apresentam risco 3,4 vezes maior de se tornarem obesos, necessitando menor energia de manutenção; 33% menos calorias para fêmeas e 28% para machos (ROOT et al, 1996a;HOWE et al, 2000, KANCHUK et al, 2002NGUYEN et al, 2004;2004b). Os estudos são controversos a respeito da obesidade em cães castrados.…”
Section: Efeitos No Metabolismo Ganho De Pesounclassified